(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Using the example of two coastal landforms of the same origin, the impact of modern climate change on their transformation and preservation is considered. The materials from the author’s field research on the Baltic and Caspian Seas were used. On the Curonian Spit, the increased frequency of severe storm surges against the background of rising water levels in the Baltic Sea has increased coastal erosion, especially in its basal part, and threatens to break through the spit into the Bay of the same name. This will lead to the dismemberment of the Curonian Spit with the formation of separate islands. Due to the lowering of the Caspian Sea level, coastal abrasion is excluded on the Gorgan Spit. The body of the spit will expand from the seaward side due to the drainage of part of the underwater coastal slope. The bay of the same name has turned into a saline and brackish swamp. Measures have been proposed to save the Curonian Spit and the Gulf of Gorgan.